Quantitative long‐term measurements of burns in a rat model using Spatial Frequency Domain Imaging (SFDI) and Laser Speckle Imaging (LSI). Issue 3 (21st February 2017) - Ponticorvo, Adrien; Burmeister, David M.; Rowland, Rebecca; Baldado, Melissa; Kennedy, Gordon T.; Saager, Rolf; Bernal, Nicole; Choi, Bernard; Durkin, Anthony J.
Abstract : Background and Ojectives: The current standard for diagnosis of burn severity and subsequent wound healing is through clinical examination, which is highly subjective. Several new technologies are shifting focus to burn care in an attempt to help quantify not only burn depth but also the progress of healing. While accurate early assessment of partial thickness burns is critical for dictating the course of treatment, the ability to quantitatively monitor wound status over time is critical for understanding treatment efficacy. SFDI and LSI are both non‐invasive imaging modalities that have been shown to have great diagnostic value for burn severity, but have yet to be tested over the course of wound healing. Methods: In this study, a hairless rat model ( n = 6, 300–450 g) was used with a four pronged comb to create four identical partial thickness burns (superficial n = 3 and deep n = 3) that were used to monitor wound healing over a 28 days period. Weekly biopsies were taken for histological analysis to verify wound progression. Both SFDI and LSI were performed weekly to track the evolution of hemodynamic (blood flow and oxygen saturation) and structural (reduced scattering coefficient) properties for the burns. Results: LSI showed significant changes in blood flow from baseline to 220% in superficial and 165% in deep burns by day 7. In superficial burns, blood flow returned to baseline levels by day 28, but not for deep burns where blood flow remained elevated. Smaller increases in blood flow were also observed in the surrounding tissue over the same time period. Oxygen saturation values measured with SFDI showed a progressive increase from baseline values of 66–74% in superficial burns and 72% in deep burns by day 28. Additionally, SFDI showed significant decreases in the reduced scattering coefficient shortly after the burns were created. The scattering coefficient progressively decreased in the wound area, but returned towards baseline conditions at the end of the 28 days period. Scattering changes in the surrounding tissue remained constant despite the presence of hemodynamic changes. Conclusions: Here, we show that LSI and SFDI are capable of monitoring changes in hemodynamic and scattering properties in burn wounds over a 28 days period. These results highlight the potential insights that can be gained by using non‐invasive imaging technologies to study wound healing. Further development of these technologies could be revolutionary for wound monitoring and studying the efficacy of different treatments. Lasers Surg. Med. 49:293–304, 2017. © 2017 Wiley Periodicals, Inc.